A Multi-Study Exploration of Factors That Optimize Hardiness in Sport Coaches and the Role of Reflective Practice in Facilitating Hardy Attitudes - Cropley, Brendan; Baldock, Lee; Hanton, Sheldon; Gucciardi, Daniel F.; McKay, Alan; Neil, Rich; Williams, Tom (Frontiers in Psychology, 2020)
Hardiness has been identified as a key personal characteristic that may moderate the ill-effects of stress on health and performance. However, little is known about how hardiness might be developed, particularly in sport coaches. To systematically address this gap, we present two linked studies. First, interviews were conducted with pre-determined high-hardy, elite coaches (n = 13) to explore how they had developed their hardy dispositions through the associated attitudinal sub-components of control, commitment, and challenge. Utilizing thematic analysis, we identified that hardiness was developed through experiential learning, external support, and the use of specific coping mechanisms. Key to all of these themes was the concept of reflective practice, which was thought to facilitate more meaningful learning from the participants’ experiences and, subsequently, enhance the self-awareness and insight required to augment hardiness and its sub-components. To investigate further the potential relationship between coaches’ reflective practices and their level of hardiness, we conducted a follow-up study. Specifically, a sample of 402 sports coaches completed the Dispositional Resilience Scale-15, the Self-Reflection and Insight Scale, and the Questionnaire for Reflective Thinking. Using latent profile analysis (LPA), we clustered participants into groups based on their reflective profiles (e.g., type of engagement, level of reflective thinking). We then examined differences in hardiness between the five latent sub-groups using multinomial regression. Findings revealed that the sub-group of highly engaged, intentionally critical reflective thinkers reported significantly higher levels of all three hardiness sub-components than all other sub-groups; these effect sizes were typically moderate-to-large in magnitude (standardized mean differences = −1.50 to −0.10). Conversely, the profile of highly disengaged, non-reflective, habitual actors reported the lowest level of all three dimensions. Collectively, our findings offer novel insights into the potential factors that may influence a coaches’ level of hardiness. We provide particular support for the importance of reflective practice as a meta-cognitive strategy that helps coaches to develop hardy dispositions through augmenting its attitudinal sub-components. Consequently, our research makes a significant contribution by providing a comprehensive insight into how we might better train and support coaches to demonstrate the adaptive qualities required to thrive in demanding situations.